PENGAWASAN MELEKAT OLEH CAMAT DALAM PENYELENGGARAAN PELAYANAN ADMINISTRASI KEPENDUDUKAN DI KECAMATAN BOGOR SELATAN KOTA BOGOR PROVINSI JAWA BARAT - Rahmawati Sururama; Hanny Febrina (PRODI ADMINISTRASI PEMERINTAHAN DAERAH FAKULTAS MANAJEMEN PEMERINTAHAN IPDN, 2019)
This study aims to find out how supervision is attached by the subdistrict head in the administration of population administration services in South Bogor District. This research is a qualitative research conducted using descriptive method, with inductive approach. Technique of data collection is done by observation, interview, and documentation. The data obtained will be analyzed by data reduction, data presentation, and conclusion and triangulation. The results showed that the supervision attached by the subdistrict head in the administration of population administration services in South Bogor District has been running quite well, especially in terms of reporting service delivery. Supporting factors inherent in supervision include the religious and socio-cultural background of society, technology, and regulations used. In addition, inhibiting factors in the form of apathetic employee behavior and leadership skills in communicating with employees. The efforts undertaken in the inherent supervision is to be an example, provide guidance and coaching personnel to employees. Suggestions that the author can convey is the implementation of inherent supervision should be guided by the Decree of the Minister of the State Apparatus Reform and Bureaucracy Number 46 of 2004 on the Guidance of Implementation of Inherent Control in Government Implementation, it is necessary to increase the supervisory element inherent, especially the elements of the procedure, as well as giving rewards and punishment should be better firmly to the employees. Keywords: inherent supervision, service, population administration